Families with Parental Mental Health Problems: A Systematic Narrative Review of Family‐Focused Practice. (26th August 2021) - Lagdon, Susan; Grant, Anne; Davidson, Gavin; Devaney, John; Donaghy, Mary; Duffy, Joe; Galway, Karen; McCartan, Claire
Abstract : The mental health problems of parents can negatively affect their whole family. The organisational and wider context may also influence the outcomes for all involved. The aims of this systematic review were: to develop a working definition of family‐focused practice (FFP); identify the types of outcomes that are measured with a focus on service user experiences; and explore how well interventions in the included studies fit with previously established components of FFP. A comprehensive literature search of 16 databases was conducted for peer‐reviewed, primary research studies related to FFP published between 1998 and 2016. In total, 3731 articles were identified and screened by four reviewers. Of those, 40 articles met all of the inclusion criteria. The review focused on family outcomes and, consistent with previous reviews, there was a reasonable degree of consistency about the core components of FFP. An additional component, identified by this review, which was part of some interventions, was work to improve access to and engagement with community supports and services. The review concludes that there is a need for: an agreed definition of FFP; clearer links to relevant theories; a more consistent approach to measuring outcomes, including economic perspectives; and an increased strategic promotion of whole family approaches. Key Practitioner Messages: There is an immediate need for an agreed definition of family‐focused practice. Relevant theory could further clarify the theories of change and anticipated outcomes. There is consistency across studies about the key components of family‐focused practice. This review suggests the inclusion of an additional component, which is practice that improves access to and engagement with community supports and services. Economic evaluations of family‐focused practice are needed. 'There is an immediate need for an agreed definition of family‐focused practice'